NORTH SUMATRA'S REGIONAL GOVERNMENT'S FINANCIAL PERFORMANCE: THE IMPACT OF LOCAL OWN REVENUE, TRANSFER REVENUE, CAPITAL EXPENDITURE, AND SILPA - Kholizah, Siti; Martini, Rita; Nurhasanah, Nurhasanah (Program Studi Diploma III Akuntansi Fakultas Ekonomi dan Bisnis Universitas Mataram, 2025)
The study is motivated by the poor level of regional financial Independence in most regencies/cities of North Sumatra Province, which largely stems from the strong dependence on transfer funds from the central government. It attempts to analyse the impact of local own revenue (LOR), transfer revenue, capital expenditure, and budget surplus (SiLPA) on the financial performance of regional governments. A quantitative approach uses panel data covering five years (2019–2023) from 32 regencies/cities, obtained from the Local Government Financial Reports published by the BPK RI. Data was analysed using panel regression analysis. The data demonstrate that LOR has a significantly positive effect on financial performance, while transfer revenue has a significantly negative impact. In contrast, capital expenditure and SiLPA have no significant effect. Simultaneously, the four independent variables influence financial performance. These findings indicate that efforts to strengthen fiscal Independence should be intensified through optimising LOR and efficiently managing transfer revenues.